Modified bioactive bone cement and preparation method thereof

By introducing bioactive polysilicon citrate-curcumin nano microspheres into PMMA bone cement, the problems of insufficient biological activity and easy loosening after implantation of PMMA bone cement were solved, and modified bioactive bone cement materials with versatility and good osteogenic activity were developed.

CN119701082APending Publication Date: 2025-03-28THE FIRST AFFILIATED HOSPITAL OF MEDICAL COLLEGE OF XIAN JIAOTONG UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411938523.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-26
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

The existing PMMA bone cement has problems such as insufficient biological activity, low autologous bone binding force, inability to directly induce bone tissue growth, and easy loosening after implantation, which limits its application in orthopedic clinical practice.

Method used

By applying bioactive polysilicon citrate-curcumin nano microspheres in PMMA bone cement, the internal microstructure is improved, mechanical properties and degradability are improved, and a multifunctional injectable bioactive bone cement material with antibacterial, anti-inflammatory, in vitro fluorescence imaging and good osteogenic activity has been developed.

Benefits of technology

It significantly improves the injectability of PMMA bone cement, reduces exothermic temperature, improves degradability, enhances the interface binding force between bone cement and bone tissue, and has good anti-inflammatory properties and the ability to promote osteogenesis and differentiation.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119701082A_ABST
    Figure CN119701082A_ABST
Patent Text Reader

Abstract

The invention discloses modified bioactive bone cement and a preparation method thereof, and relates to the technical field of biomedical materials, the preparation method comprises the following steps: S1, preparing a poly-citric acid siloxane hybrid prepolymer; s3, preparing the poly (citric acid siloxane)-curcumin nano-microsphere modified bioactive bone cement: dissolving the poly (citric acid siloxane)-curcumin nano-microsphere in an ethanol solution, then adding methyl methacrylate, and uniformly mixing and stirring, so as to obtain a liquid-phase component; and mixing the polymethyl methacrylate powder with the liquid-phase component, quickly stirring for 3 minutes, and defoaming to obtain the modified bioactive bone cement. The modified bioactive bone cement disclosed by the invention has good operation performance and more matched mechanical strength, and also has biological multifunctionality including antibacterial property, anti-inflammatory property, in-vitro fluorescence imaging, good osteogenic activity and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of biomedical materials, and in particular to a modified bioactive bone cement and a preparation method thereof. Background Art

[0002] Polymethyl methacrylate (PMMA) bone cement is widely used as an injectable filling material in orthopedics. Although it has good injectability, rapid curing and excellent mechanical properties, PMMA bone cement itself cannot be degraded, lacks biological activity, has low interfacial bonding strength with autologous bone, and cannot directly induce bone tissue growth. After being implanted in the body for a period of time, the material is prone to loosening, resulting in implant failure, which greatly limits its clinical application.

[0003] Although some progress has been made in the modification of PMMA bone cement at home and abroad, there is still a lack of bone repair materials that meet the ideal requirements of doctors in clinical practice. The defects of existing modification technologies are as follows: (1) Adding bioactive fillers to PMMA bone cement is the most common and effective method to improve the bioactivity of PMMA bone cement. Previous researchers simply mixed fillers and bone cement without considering the internal microstructure of bone cement, which resulted in the fillers added to bone cement not being able to play a good role, and the addition of fillers would also cause changes in the comprehensive properties of bone cement. (2) Bioactive materials often have poor mechanical properties, so the mechanical compressive strength of modified PMMA bone cement is greatly reduced. It may be suitable for patients with osteoporosis, but for people with normal bone quality, it should be selected with caution. (3) Some degradable materials have a good degradation rate in in vitro tests (simulated body fluids), but the human body fluid environment is complex, and the degradation rate of the material in the body is slow, which is lower than the growth rate of new bone tissue, which easily leads to the inability of osteoblast bone mineralization and bone regeneration bone tissue to grow into PMMA pores, greatly reducing the efficiency of the implant material and bone forming a whole. (4) The bioactivity-related indicators of the modified materials are not satisfactory. Some modified materials have the "bottleneck" problem of cytotoxicity, which is not conducive to the subsequent clinical trials.

[0004] Based on this, it is very meaningful to develop a safe bioactive bone cement that improves the internal microstructure of the polymer, enhances mechanical properties, improves degradability, and has biological multifunctionality. Summary of the invention

[0005] In view of the above problems, the present invention provides a modified bioactive bone cement and its preparation method and application. Based on PMMA, the present invention uses bioactive polycitrate silicon-curcumin nano-microspheres to improve it and develop a multifunctional injectable bioactive bone cement material with good operating performance and more matched mechanical strength, and at the same time has antibacterial, anti-inflammatory, in vitro fluorescence imaging and good osteogenic activity.

[0006] In order to achieve the above object, the technical solution adopted by the present invention is as follows: The present invention provides a method for preparing a modified bioactive bone cement, comprising the following steps: S1: Preparation of polycitrate siloxane hybrid prepolymer: melt citric acid at a constant nitrogen flow rate of 160°C for 20 min, then add 1,8-octanediol and 3-aminopropyltriethoxysilane at 140°C, stir and react for 60 min; add dimethyl sulfoxide to the reaction product, continue stirring for 10 min, then dialyze and freeze-dry to obtain polycitrate siloxane hybrid prepolymer (PCS), which is stored for future use; the entire reaction is carried out under nitrogen environment, and the synthesis route is as follows:

[0007] Silane can be grafted onto the side chain of the prepolymer through a chemical reaction between the amino and carboxyl groups of citric acid. During the synthesis process, due to the presence of water after polycondensation, silane and Si-OH undergo hydrolysis and polycondensation to form multifunctional PCS.

[0008] S2: Preparation of polycitrate siloxane-curcumin nanospheres: S21: dissolving Pluronic F-127 in deionized water to prepare a 12.5 wt % Pluronic F-127 aqueous solution; S22: dissolving the polycitrate siloxane hybrid prepolymer in tetrahydrofuran to prepare a 20 wt% polycitrate siloxane solution; adding curcumin to the polycitrate siloxane solution, and stirring with a magnetic stirrer until fully dissolved to obtain a polycitrate siloxane-curcumin (PCS-curcumin) polymer solution; S23: adding the Pluronic F-127 aqueous solution to the centrifuge tube, and then slowly adding the PCS-curcumin polymer solution, and rapidly stirring to mix them evenly to obtain a mixed solution; S24: stirring the mixed solution at high speed for 2 h using a high-speed dispersing mixer to form a uniform emulsion; S25: The emulsion was centrifuged for 5 min, the precipitate was removed, the supernatant was collected, and freeze-dried using a freeze dryer to obtain polycitrate siloxane-curcumin nanospheres (PCS-curcumin nanospheres or PCS nanospheres), which were stored in a dry and cool place for future use. The synthesis route is as follows:

[0009] S3: Preparation of PCS nanosphere modified bioactive bone cement: dissolve PCS nanospheres in ethanol solution, add methyl methacrylate (MMA) and mix well to obtain a liquid phase component; then mix polymethyl methacrylate (PMMA) powder with the liquid phase component, stir rapidly for 3 minutes, and degas to obtain modified bioactive bone cement (PCS / PMMA bioactive bone cement).

[0010] Furthermore, in step S1, the molar ratio of citric acid, 1,8-octanediol and 3-aminopropyltriethoxysilane is 1.0:1.0:0.4.

[0011] Furthermore, in step S22, the amount of curcumin used is 5% of the mass of the polycitrate siloxane hybrid prepolymer.

[0012] Furthermore, in step S23, the volume ratio of the Pluronic F-127 aqueous solution to the polycitrate siloxane-curcumin polymer solution is 3:1.

[0013] Furthermore, in step S24, the stirring speed is 20000 r / min.

[0014] Furthermore, in step S25, the centrifugal speed is 5000 r / min.

[0015] Furthermore, in step S3, the mass ratio of polycitrate siloxane-curcumin nanospheres, ethanol and methyl methacrylate is 10:3:25; the mass ratio of polymethyl methacrylate powder to methyl methacrylate is 2:1.

[0016] The present invention also provides a modified bioactive bone cement prepared by the preparation method of the modified bioactive bone cement.

[0017] From the research purpose, the main modification strategy of previous bioactive bone cement is to improve the immune inflammatory response of bone cement implanted in the body and reduce the fiber wrapping around bone cement, but this does not fundamentally solve the postoperative loosening of implants. From the perspective of inducing osteogenic differentiation, the present invention enhances bone integration through the osteogenic effect of bone cement in the body, and enhances the postoperative stability of intervertebral body through bony fusion, which not only reduces aseptic inflammation after implantation of bone cement, but also reduces the postoperative loosening caused by implants through the osteogenic effect. At the same time, adding small molecule curcumin to the composite active material can increase the anti-inflammatory activity and reduce the formation of fiber wrapping.

[0018] From the point of view of modification strategy, researchers in the past simply mixed fillers and bone cement without considering the internal microstructure of bone cement. This has led to the fillers added to bone cement not being able to play a good role, and the addition of fillers will also cause changes in the comprehensive properties of bone cement. The present invention prepares partially degradable bone cement by adding degradable nano-microspheres of specific size and regular shape, which can promote the growth of new bone tissue, strengthen the interface bonding force between bone cement and bone tissue, and the added degradable microspheres have certain biocompatibility and osteogenesis ability, and the microenvironment produced by degradation can promote the growth of new bone formation and bone tissue.

[0019] Compared with the prior art, the present invention has the following beneficial effects: In the present invention, bioactive polycitrate silicon-curcumin nanospheres (PCS nanospheres) were synthesized for the first time, and PCS / PMMA bioactive bone cement was prepared using them as mechanical and activity enhancing phases. The properties of PMMA such as injectability, lowering exothermic temperature, and improving degradability were significantly improved, and the elastic modulus of PCS / PMMA bioactive bone cement was more compatible with vertebral bone. In addition, compared with the single function of other modified bone cements, PCS / PMMA bioactive bone cement has biological multifunctionality, including good hydrophilicity, antioxidant properties, in vitro induced mineralization, and good anti-inflammatory properties. At the same time, in vitro and in vivo tests also confirmed that it has the ability to promote osteogenic differentiation and anti-inflammatory properties. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 This is a physical picture of PCS-curcumin nanoparticles according to an embodiment of the present invention; Figure 2 This is a diagram showing the injectability test results of the modified (PCS / PMMA) bioactive bone cement of the present invention; Figure 3 It is an infrared thermal image of the modified (PCS / PMMA) bioactive bone cement of the present invention; Figure 4 It is a graph showing the change of polymerization temperature of the modified (PCS / PMMA) bioactive bone cement over time; Figure 5 (a) The naked eye observation picture and (b) SEM electron microscope picture of the modified (PCS / PMMA) bioactive bone cement of the present invention after degradation for 6 weeks; Figure 6 : (a) compression test diagram and (b) compression strength quantitative diagram of the modified (PCS / PMMA) bioactive bone cement of the present invention; Figure 7 The water contact angle measurement diagram of (a) PMMA bone cement and (b) modified (PCS / PMMA) bioactive bone cement of the present invention; Figure 8This is a comparison chart of the in vitro antioxidant properties of the PMMA bone cement of the present invention and the modified (PCS / PMMA) bioactive bone cement; Fig. 9 The present invention is (a) a SEM electron microscope image of PCS / PMMA bioactive bone cement, (b) a SEM electron microscope image of PMMA bone cement, (c) an EDS energy spectrum image of PCS / PMMA bioactive bone cement, and (d) an EDS energy spectrum image of PMMA bone cement; Fig.10 It is a diagram showing the anti-inflammatory effects of PMMA bone cement and PCS / PMMA bioactive bone cement of the present invention; Fig.11 It is a general view of the bone defect samples of PCS / PMMA bioactive bone cement and PMMA bone cement at 6 weeks and 12 weeks of the present invention; Fig.12 The figures are the results of the mechanical test on the push-out of bone cement at the bone defect site of the present invention, (a) the displacement-push-out force curves of PCS / PMMA bioactive bone cement and PMMA bone cement at 6w and 12w; (b) the maximum push-out force comparison of PCS / PMMA bioactive bone cement and PMMA bone cement at 6w and 12w. DETAILED DESCRIPTION

[0021] In order to make the purpose and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0022] The instruments, reagents, materials, etc. involved in the following examples, unless otherwise specified, are all conventional instruments, reagents, materials, etc. in the prior art and can be obtained through regular commercial channels. The experimental methods, detection methods, etc. involved in the following examples, unless otherwise specified, are all conventional experimental methods, detection methods, etc. in the prior art.

[0023] In this embodiment, DMEM low-glucose culture medium was purchased from Gibco, with item number: C11885500BT, batch number: 8123145; components: D-glucose (1 g / L); sodium pyruvate (110 mg / L), and L-glutamine.

[0024] Example 1 This embodiment provides a modified bioactive bone cement, and the preparation method thereof is as follows: S1: Preparation of polycitrate siloxane hybrid prepolymer: 1703.5 mg of citric acid was melted at 160°C under a constant nitrogen flow rate for 20 min, and then 1296.5 mg of 1,8-octanediol and 785.08 mg of 3-aminopropyltriethoxysilane (the molar ratio of citric acid, 1,8-octanediol and 3-aminopropyltriethoxysilane was 1.0:1.0:0.4) were added at 140°C, stirred and further reacted for 60 min; dimethyl sulfoxide (DMSO) was added to the reaction product, and stirring was continued for 10 min, and then after dialysis and freeze-drying, polycitrate siloxane hybrid prepolymer (PCS) was obtained and stored for future use; the entire reaction was carried out under nitrogen environment; S2: Preparation of polycitrate siloxane-curcumin nanospheres (modified nanospheres): S21: dissolving Pluronic F-127 in deionized water to prepare a 12.5 wt % Pluronic F-127 aqueous solution; S22: dissolving a polycitrate siloxane hybrid prepolymer in tetrahydrofuran to prepare a 20 wt% polycitrate siloxane solution; adding curcumin (the amount of curcumin is 5% of the weight of the polycitrate siloxane hybrid prepolymer) to the polycitrate siloxane solution, and stirring with a magnetic stirrer until fully dissolved to obtain a polycitrate siloxane-curcumin (PCS-curcumin) polymer solution; S23: Add 15 mL of Pluronic F-127 aqueous solution to a 50 mL centrifuge tube, then slowly add 5 mL of PCS-curcumin polymer solution (the volume ratio of the two is 3:1), and stir quickly to mix them evenly to obtain a mixed solution; S24: stirring the mixed solution at a speed of 20000 r / min for 2 h using a high-speed disperser to form a uniform emulsion; S25: The emulsion was centrifuged at 5000 r / min for 5 min, the precipitate was removed, the supernatant was collected, and freeze-dried using a freeze dryer to obtain polycitrate siloxane-curcumin nanospheres (PCS-curcumin nanospheres or PCS nanospheres), which were stored in a dry and cool place for future use; see the attached picture for the actual product. Figure 1 ; S3: Preparation of PCS nanosphere modified bioactive bone cement: dissolve PCS nanospheres in ethanol solution, add methyl methacrylate (MMA) and stir evenly to obtain a liquid phase component; then mix polymethyl methacrylate (PMMA) powder with the liquid phase component (the mass ratio of nanospheres, ethanol, MMA, and PMMA is 10:3:25:50), stir rapidly for 3 minutes, and after degassing, the modified bioactive bone cement (PCS / PMMA bioactive bone cement) is obtained.

[0025] Comparative Example 1 Commercially available PMMA bone cement (Xi'an Heraeus bone cement agent, batch: 68741305, model: PALACOSLV).

[0026] The PCS / PMMA bioactive bone cement after degassing in Example 1 and the PMMA bone cement in Comparative Example 1 were respectively injected into the prefabricated mold, and a certain pressure was applied to fully fill every corner and fine part of the mold. Under a certain temperature and pressure, the bone cement after the molding treatment was cured to form a stable solid model. After curing, the solid model was taken out of the mold, and necessary trimming and polishing were performed for subsequent test use.

[0027] Experimental Example 1 The following tests were performed on the PCS / PMMA bioactive bone cement of Example 1 and the PMMA bone cement of Comparative Example 1: (1) Injectability test To test the injectability of bone cement, PCS / PMMA bioactive bone cement was stirred and then transferred to a 5 mL syringe with a 10 mm nozzle to ensure that there were no air bubbles. The plunger was pushed at a constant speed to extrude the bone cement, and the extruded amount was recorded. The percentage of injectability was calculated by the formula injectability (%) = (W2-W3) / (W2-W1) × 100%, where W1 is the weight of the empty syringe, W2 is the weight of the syringe filled with bone cement, and W3 is the weight of the syringe after extrusion. Each sample was tested three times and the average value was taken to reduce the error.

[0028] Depend on Figure 2 It can be seen from the results that the modified bioactive bone cement prepared in this example has good injectability.

[0029] (2) Polymerization temperature test The maximum polymerization temperature of bone cement was measured using infrared thermal imaging technology. First, PCS / PMMA bioactive bone cement and PMMA bone cement were filled into the mold respectively to ensure that they were filled and bubbles were excluded. Then, the infrared thermal imager parameters were set, including a wavelength range of 8-14μm, a frame rate of 30 frames / second, a fast scanning rate, and a measurement range of -50~300℃ with an accuracy of ±2℃. The mold was placed under the thermal imager and the temperature changes during the polymerization process were recorded every 10 seconds and photographed. Finally, the data was imported into the Origin software, the time-temperature curve was plotted, and the peak temperature was observed. Each sample was tested three times, and the average value was taken as the final polymerization peak temperature.

[0030] Depend on Figure 3 It can be seen that the central polymerization temperature of the modified bioactive bone cement (PCS / PMMA) is relatively low; Figure 4The curve of temperature change over time during the polymerization process shows that the maximum polymerization temperature of the modified bioactive bone cement (PCS / PMMA) (99.8°C) is lower than that of PMMA bone cement (67.1°C).

[0031] (3) Degradability test Prepare modified bioactive bone cement disc samples of the same size and shape, dry and label them. Soak the samples in PBS with a pH of 7.40, and the ratio of PBS volume to sample surface area is 10 mL / cm 2 The samples were placed in a constant temperature shaking incubator at 37°C and 80 rpm, and their morphology was observed with the naked eye and under an electron microscope after 6 weeks.

[0032] Depend on Figure 5 As can be seen from Figures 5a and 5b, after 6 weeks, the modified bioactive bone cement has a porous structure left after degradation both under the naked eye and electron microscope, indicating that the degradability is enhanced.

[0033] (4) Compressive strength test Group design: 4 groups of bone cements with different contents were designed, in which the mass ratios of PCS-curcumin nanospheres to PMMA solid phase components were 0% (without modified nanospheres), 5% (1:20), 10% (1:10), and 20% (1:5, the same as in Example 1) of bone cement, and each group of bone cement was recorded as PMMA, 5PCS, 10PCS, and 20PCS, respectively.

[0034] Four groups of bone cement with different contents were made into solid model samples, placed in the mold to ensure that there was no gap, and the mold was fixed between the upper and lower platens of the universal mechanical testing machine with a fixture ( Figure 6 a). Set the test machine parameters: test speed 20mm / min, ambient humidity 50% relative humidity, force sensor accuracy ±0.5% full scale, displacement sensor accuracy ±0.01mm, data recording frequency once per second. Perform 5 tests on each sample to improve accuracy.

[0035] After the test, the recorded data is input into the Origin software to automatically generate a force-displacement curve. According to the curve shape and data points, the compressive strength of the sample is calculated using the formula: σ=4P / πD², where σ is the compressive strength (MPa), P is the maximum pressure (N), and D is the sample diameter (mm).

[0036] Depend on Figure 6 From the quantitative results of compressive strength of b, it can be seen that compared with PMMA, the compressive strength of 20PCS, 10PCS, and 5PCS is reduced, which can reduce the stress shielding effect of the contact between the material and the bone to a certain extent. At the same time, it is still higher than the international standard of compressive strength of bone cement materials (70 MPa).

[0037] (5) Hydrophilicity test The hydrophilicity of the modified bioactive bone cement samples was evaluated by a water contact angle measuring machine (SL200KB, Kino). The surface hydrophilicity of the material was defined by the size of the contact angle formed between the tangent line drawn at the solid surface and the droplet. The smaller the contact angle, the better the hydrophilicity of the material.

[0038] Depend on Figure 7 The water contact angle measurement results of a and 7b show that, compared with PMMA, the water contact angle of the modified bioactive bone cement (PCS / PMMA) of this embodiment is smaller, indicating that the hydrophilicity of the modified bioactive bone cement of this embodiment is improved and has good hydrophilicity.

[0039] (6) Antioxidant test - in vitro antioxidant test (ROS scavenging test) The antioxidant properties of bone cement materials were evaluated by detecting their ability to scavenge DPPH free radicals. PCS / PMMA and PMMA samples were placed at the bottom of the culture plate, and 300 μL of 1000 μM DPPH methanol solution was added to ensure uniform coverage. Then, the culture plate was placed in a constant temperature shaker at 37°C and incubated in the dark to keep the pH value and ion concentration of the solution stable. After the incubation, the mixture was transferred to a centrifuge tube and centrifuged at 8000 rpm for 5 minutes. The color change of the supernatant was observed and recorded. The control group used 5 μL of 10 mM ascorbic acid (Vc) methanol solution, and then added 300 μL DPPH methanol solution, and the same steps were followed for treatment and measurement.

[0040] Depend on Figure 8 It can be seen that the color of the free radicals of the modified bioactive bone cement becomes lighter, but is weaker than that of the reducing agent vitamin C.

[0041] (7) In vitro mineralization experiment Prepare PMMA and PCS / PMMA bone cement discs respectively, ensuring that their size and shape are consistent for comparison experiments. Immerse the discs in the corresponding modified simulated body fluid (SBF) to ensure that the discs are in full contact with the solution. The specific surface area of ​​the discs to the volume of SBF is 0.1 cm 2 / cm 3 The samples were placed in a constant temperature oscillator at 37°C and kept oscillating. The SBF solution was replaced every 3 days to maintain the stability of ion concentration and pH value.

[0042] After immersion for 14 days, the bone cement discs were taken out, washed with deionized water to remove ions and impurities attached to the surface, and then dried at 25°C. Finally, the surface morphology changes of the dried discs were observed using a scanning electron microscope (SEM), and elemental analysis was performed using an energy dispersive spectrometer (EDS) to determine the formation of apatite.

[0043] Fig. 9 a, 9b electron microscopy shows the formation of mineralization products similar to hydroxyapatite. Fig. 9 The EDS spectra of c and 9d also show a higher distribution of Ca elements, indicating that PCS / PMMA bioactive bone cement has a good in vitro mineralization effect.

[0044] (8) Anti-inflammatory performance test The circular slides for culturing macrophages were disinfected and placed at the bottom of a 24-well plate. Next, RAW264.7 cells were inoculated on the slides and, after 12 hours of attachment, were divided into four groups: normal group (NC group), LPS group, LPS+PMMA group, and LPS+PCS / PMMA group. The normal group was treated with conventional culture medium (DMEM low-glucose culture medium + 10% FBS serum + 1% penicillin-streptomycin antibiotics), and the other three groups were stimulated with 400ng / mL LPS for 18 hours. Subsequently, the LPS group was replaced with conventional culture medium, and the LPS+PMMA group and LPS+PCS / PMMA group were cultured with the extracts of PCS / PMMA bioactive bone cement and PMMA bone cement, respectively. The culture was continued for 2 days to observe the cell growth status.

[0045] After the culture, the cells were stained with DCFH-DA probe and incubated at 37°C for 30 minutes. Then, the green fluorescence of the cells was observed using a laser confocal microscope, and the fluorescence intensity and distribution of each group were recorded to explore the effects of different extracts on ROS generation in macrophages.

[0046] Depend on Fig.10 It can be seen that PCS / PMMA bioactive bone cement has a good ability to remove intracellular ROS and has a good anti-inflammatory effect.

[0047] (9) Osteogenic activity A rat femoral condyle bone defect model was constructed. PCS / PMMA bioactive bone cement, PMMA bone cement, and a blank group (Blank) without any material were implanted surgically. Samples were taken at 6 weeks and 12 weeks after surgery. The bone cement in the femoral condyle bone defect sites of the three groups was pushed out and observed with the naked eye. The main focus was on the healing of the bone defect area, including defect morphology, size changes, contours and boundaries, as well as contact with surrounding bone tissue and new bone formation. At the same time, the response of the bone tissue around the defect was observed, and the color, texture and structural changes, such as bone hyperplasia, bone bridge formation, and the blur or sharpness of the defect edge, were noted. At the same time, a push-out mechanical experiment was performed to evaluate the bone integration performance of the modified bone cement material implant. First, cubic samples of the same size were cut from the femoral condyle specimens of fresh bone cement implants. The samples were fixed using a multifunctional material mechanical testing machine, and an axial compressive load was applied with a stainless steel rod with a diameter of 2 mm. The loading speed was set to 1 mm / min. During the experiment, the load was applied, and the stress and displacement were recorded until the interface between the implant and the bone was destroyed, and the maximum push-out force was recorded. Finally, stress-displacement curves were plotted to evaluate the bonding strength of the bone-implant-bone interface using the maximum push-out force, and different sample groups were compared to analyze the effects of materials or processing conditions on the bone integration performance.

[0048] Fig.11 It can be seen that the bone defect in the PCS / PMMA bioactive bone cement group became smaller. Fig.12 a and 12b, it can be seen that the push-out force of the PCS / PMMA bioactive bone cement group is greater, indicating that the bone integration of the modified bioactive bone cement is more solid.

[0049] In this embodiment, bioactive polycitrate silicon-curcumin nanospheres (PCS nanospheres) were synthesized for the first time, and PCS / PMMA bioactive bone cement was prepared using them as mechanical and activity enhancement phases. The injectability, exothermic temperature, and degradability were significantly improved, and the elastic modulus of PCS / PMMA bioactive bone cement was more compatible with vertebral bone. In addition, compared with the single function of other modified bone cements, PCS / PMMA bioactive bone cement has biological multifunctionality, including good hydrophilicity, antioxidant properties, in vitro induced mineralization, and good anti-inflammatory properties. At the same time, in vitro and in vivo tests also confirmed that it has the ability to promote osteogenic differentiation and anti-inflammatory properties.

[0050] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing a modified bioactive bone cement, characterized in that: The specific steps include: S1: Preparation of polycitrate siloxane hybrid prepolymer: melt citric acid at 160°C under a constant nitrogen flow rate for 20 min, then add 1,8-octanediol and 3-aminopropyltriethoxysilane at 140°C, stir and further react for 60 min; add dimethyl sulfoxide to the reaction product, continue stirring for 10 min, then dialyze and freeze-dry to obtain polycitrate siloxane hybrid prepolymer, which is stored for later use; S2: Preparation of polycitrate siloxane-curcumin nanospheres: S21: dissolving Pluronic F-127 in deionized water to prepare a 12.5 wt % Pluronic F-127 aqueous solution; S22: dissolving the polycitrate siloxane hybrid prepolymer in tetrahydrofuran to prepare a 20 wt% polycitrate siloxane solution; adding curcumin to the polycitrate siloxane solution, and stirring with a magnetic stirrer until fully dissolved to obtain a polycitrate siloxane-curcumin polymer solution; S23: adding the Pluronic F-127 aqueous solution to the centrifuge tube, and then slowly adding the polycitrate siloxane-curcumin polymer solution, and rapidly stirring to mix them evenly to obtain a mixed solution; S24: stirring the mixed solution at high speed for 2 h using a high-speed dispersing mixer to form a uniform emulsion; S25: centrifuging the emulsion for 5 min, removing the precipitate, collecting the supernatant, and freeze-drying it using a freeze dryer to obtain polycitrate siloxane-curcumin nanoparticles, which are stored in a dry and cool place for future use; S3: Preparation of polycitrate siloxane-curcumin nanospheres modified bioactive bone cement: dissolve polycitrate siloxane-curcumin nanospheres in ethanol solution, add methyl methacrylate and mix well to obtain a liquid phase component; then mix the polymethyl methacrylate powder with the liquid phase component, stir rapidly for 3 minutes, and degas to obtain the modified bioactive bone cement.

2. The method for preparing a modified bioactive bone cement according to claim 1, characterized in that: In the step S1, the molar ratio of citric acid, 1,8-octanediol and 3-aminopropyltriethoxysilane is 1.0:1.0:0.

4.

3. The method for preparing a modified bioactive bone cement according to claim 1, characterized in that: In the step S22, the amount of curcumin used is 5% of the weight of the polycitrate siloxane hybrid prepolymer.

4. The method for preparing a modified bioactive bone cement according to claim 1, characterized in that: In the step S23, the volume ratio of the Pluronic F-127 aqueous solution to the polycitrate siloxane-curcumin polymer solution is 3:

1.

5. The method for preparing a modified bioactive bone cement according to claim 1, characterized in that: In step S24, the stirring speed is 20000 r / min.

6. The method for preparing a modified bioactive bone cement according to claim 1, characterized in that: In step S25, the centrifugal speed is 5000 r / min.

7. The method for preparing a modified bioactive bone cement according to claim 1, characterized in that: In the step S3, the mass ratio of polycitrate siloxane-curcumin nanospheres, ethanol and methyl methacrylate is 10:3:25; the mass ratio of polymethyl methacrylate powder to methyl methacrylate is 2:

1.

8. A modified bioactive bone cement prepared by the method for preparing the modified bioactive bone cement according to any one of claims 1 to 7.